2009
DOI: 10.1523/jneurosci.4089-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

An Auditory Region in the Primate Insular Cortex Responding Preferentially to Vocal Communication Sounds

Abstract: Human imaging studies implicate the insular cortex in processing complex sounds and vocal communication signals such as speech. In addition, lesions of the insula often manifest as deficits in sound or speech recognition (auditory agnosia) and speech production. While models of acoustic perception assign an important role to the insula, little is known about the underlying neuronal substrate. Studying a vocal primate, we identified a predominantly auditory region in the caudal insula and therein discovered a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
100
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 92 publications
(132 reference statements)
13
100
2
Order By: Relevance
“…Some research has found increased gray matter density localized in the right anterior insula-a key hub within the salience network, a collection of brain regions involved in the detection and evaluation of motivationally relevant stimuli (Hölzel et al 2008;Seeley et al 2007). By contrast, the present investigation observed increased cortical thickness within the left posterior insula-a region implicated in auditory processing and interoception (Bamiou et al 2003;Remedios et al 2009;Flynn 1999;Farb et al 2012).…”
Section: Cortical Thickness Changes In the Posterior Insulacontrasting
confidence: 86%
See 1 more Smart Citation
“…Some research has found increased gray matter density localized in the right anterior insula-a key hub within the salience network, a collection of brain regions involved in the detection and evaluation of motivationally relevant stimuli (Hölzel et al 2008;Seeley et al 2007). By contrast, the present investigation observed increased cortical thickness within the left posterior insula-a region implicated in auditory processing and interoception (Bamiou et al 2003;Remedios et al 2009;Flynn 1999;Farb et al 2012).…”
Section: Cortical Thickness Changes In the Posterior Insulacontrasting
confidence: 86%
“…Another study showed changes in posterior insular function and connectivity linked to interoception as a function of mindfulness training (Farb et al 2012). The posterior insula is a region of particular interest to the present research because of its implication in auditory and interoceptive processing by both structural and functional neuroimaging research (Bamiou, Musiek, & Luxon 2003;Remedios, Logothetis, & Kayser 2009;Flynn 1999) and due to the previously demonstrated effect of mindfulness training on the activation and functional connectivity of this region (Kilpatrick et al 2011;Farb et al 2012;Kirk, Gu, Harvey, Fonagy, & Montague 2014). Changes in cortical thickness of the posterior insula may lead to changes in auditory processing, and the posterior insula may interact with other regions implicated in auditory processing, such as the left middle/superior temporal gyrus (MTG/STG) and right ventrolateral prefrontal cortex (vlPFC) in a network involved in the detection of novel auditory information (Petrides & Pandya 2002;Plakke & Romanski 2014;Rauschecker & Scott 2009;Schönwiesner et al 2007;Buse & Roessner 2016;Kiehl, Laurens, Duty, Forster, & Liddle 2001).…”
mentioning
confidence: 91%
“…However, numerous human voices (friends, celebrities) were also effective inducers. Voice-selective cortical areas have been documented in superior temporal cortex (Belin, Lafaille, Ahad, & Pike, 2000;Petkov et al, 2008) and insular cortex (Remedios, Logothetis, & Kayser, 2009). These areas may show an increased connectivity to gustatory Lexical-gustatory synesthesia 13 cortex in PS independently of the hyperconnectivity between language cortex and gustatory cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-tensor imaging data in a case of auditory interval-gustatory synesthesia have suggested a hyperconnectivity between auditory cortex and gustatory cortex (Hänggi, Beeli, Oechslin, & Jäncke, 2008). However, the insula appears to be involved in auditory and phonological processing in addition to gustatory processing (Bamiou, Musiek, & Luxon, 2003;Remedios et al, 2009) and in cross-modal sensory interactions involving auditory input (Kimura, Imbe, & Donishi, 2010), and thus a local hyperconnectivity in the insula could also be involved. PS also reported pain and visceral sensations, modalities which are strongly represented in the insula.…”
Section: Discussionmentioning
confidence: 99%
“…To characterize the statistical properties of response latencies we computed the following quantities from the distribution of single-trial latencies of each neuron: (1) the mean latency (across trials and stimuli), (2) the fraction of responsive trials in which a well defined latency could be detected, (3) the latency variability, computed as the SD of the latency over all responsive trials to each stimulus, and then averaged across stimuli. The selectivity of each neuron was determined using the "50% of maximal response" criterion (Tian et al, 2001;Remedios et al, 2009): for each stimulus we computed the average firing rate during the 300 ms window. From this we computed the fraction of stimuli for which this firing rate was larger than half the maximal of all these 12 responses.…”
Section: Quantification Of Single-trial Response Latencies and Of Resmentioning
confidence: 99%